Relationship between The Education of Parents and Democratic Update Patterns To The Social Development of Early Ages - Juarus Ilma, Rhosma (Early Childhood Research Journal (ECRJ), 2020)
From the results that have been examined, it can be concluded that there is a relevant relationship between the educational background of parents and democratic parenting towards the social development of early childhood in the village of Bandar Magetan. this incident can be seen from the magnitude of r square of 33.6% can be interpreted the higher level of parental education resulted in parents increasingly understanding good parenting to help social development of young children.From the research also can be underlined the existence of democratic parenting can be influenced by the age of parents and educational background in order to support the social development of children.